Améliorer le sentiment de compétence en gestion de projet des étudiants : résultats d’une démarche SoTL - Najoua Mohib; Simon Zingaretti; Rémi Bachelet (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This paper presents the results of a scholarship of teaching and learning study, which has been conducted in order to improve project management instruction for students enrolled in the second year of the Master of Educational Sciences at the University of Strasbourg. After we noticed that students didn’t feel ready for leading a project at the end of their program, we have developed a new pedagogical approach based on the Self-Efficacy Theory (Bandura, 2003). The aim of the SoTL work, initiated at the same time, was to examine whether the introduction of the verbal persuasion instructional model had a more positive effect on the project management self-competency than the learning-by-doing approach used previously. So, students have been invited to assess themselves on the 24 competencies targeted by this course, at three moments : before, during and after their program experience. Semi-structured interviews were also conducted with all the participants. While results show a significant increase in project management self-competency, it has been impossible to establish a strong relationship with either of both pedagogical approach. However, the results of this experience were very positive and some strategies for practice have been suggested for the future. This contribution ends with a reflection on our own experience of the SoTL approach.